Obstacles to the application of organizational change in the institutes of science and techniques of physical and sports activities ""Total quality management as a model - metarfi, khemissi; merniz, amna (Journal of Social Sciences and Humanities, 2020)
This Study was undertaken to explore the different obstacles faced when applying the Total Quality Management (i.e., TQM) in institutions of Science and Techniques of Physical and Sports Activities. The study for exploring, particularly the attitudes of administrators at the institution of Science and Techniques of Physical and Sports Activities; M’sila University. This research was based on the use of the analytical, descriptive approach simply because it is proper to the aim of this investigation. Hence, the researcher used a questionnaire which was distributed to a sample population of 31 employees who work at the institution of Science and Techniques of Physical and Sports Activities; M’sila University. The results gathered from this study concludes that Regarding the obstacles related to the leadership aspect, the results gathered to prove different constraints which mostly include the lack of clarity of TQM Implementation Policy, lack of maintaining an ongoing contact with the higher management with administrators and officials Quality Assurance Committee about the ways in which the real application of TQM can be applied, and about the obstacles related to the behavioral aspect of members concerned with the application of quality, the data gathered showed also different constraints which mostly incorporate fear of the evaluation process, fear of being unable to respond to the nature of the new tasks, and fear of losing power.